Foundation literature in sociological approaches - BENRAMDHANE, Samia (Social Sciences Journal)
This study addresses the subject of conceptual connotations of the institution in the context of the sociological approach, because the concept is today witnessing a substantial intellectual changes imposed by the nature of what is seen in communities of social and economic transformations as a result of the accumulation of Tribal Research, it confirmed the literature of contemporary regulatory and studies it. For this study it aims to monitor the most important sociological approaches that dealt with the evolution of the enterprise concept that accompanied the beginnings of the emergence of sociology as a discipline autonomous from other disciplines of social sciences, and this is the basis of approaches intellectual sociological classic to modern approaches sociological that contributed to regeneration in handling intellectual and theoretical and systematic interpretation of the institution and principles, in order to stability. In addition to the detection of the most important changes between disparate approaches in the sociological interpretation of the concept of the institution.